Controlled Sequential Assembly of Metal–Organic Polyhedra into Colloidal Gels with High Chemical Complexity. Issue 8 (4th May 2022) - Tsang, Min Ying; Tokuda, Shun; Han, Po-Chun; Wang, Zaoming; Legrand, Alexandre; Kawano, Marina; Tsujimoto, Masahiko; Ikeno, Yuki; Urayama, Kenji; Wu, Kevin C.-W.; Furukawa, Shuhei
Abstract : Assembling many chemical components into a material in a controlled manner is one of the biggest challenges in chemistry. Particularly, porous materials with multivariate character within their scaffolds are expected to demonstrate synergistic properties. In this study, a synthetic strategy to construct porous networks with multiple chemical components is shown. By taking advantage of the hierarchical nature of a colloidal system based on metal–organic polyhedra (MOPs), a two‐step assembly process to form colloidal networks is developed, assembling MOPs with the organic linker to form a MOP network as a colloidal particle, followed by further connection of colloids by additional cross‐linkers to construct colloidal networks. This synthetic process allows the use of different organic linkers not only for connecting MOPs and colloidal particles, respectively, but also for assembling different colloidal particles formed by various MOPs. The proof of concept of this tunable multivariate colloidal gel system offers an alternative to developing functional porous soft materials with multifunction. Abstract : Assembly of metal–organic polyhedra (MOPs) to colloids gels via a step‐by‐step approach allows the formation of multivariate network. The possibility to connect the components with coordinative cross‐linkers in a controlled manner can generate more complexed functionality at the macroscale. Herein, this methodology increases the chemical complexity of the system that is crucial for tailoring material properties.